2019
DOI: 10.1139/tcsme-2018-0234
|View full text |Cite
|
Sign up to set email alerts
|

A brief review of condition monitoring techniques for the induction motor

Abstract: The induction motor is widely used in industry owing to its simple construction and low cost. In this paper, we present a state-of-the-art review of condition monitoring techniques for the induction motor. As the induction motor is used in many production processes, its uninterrupted and cost-effective functioning is of prime importance. Condition monitoring of the induction motor enables detection and prediction of different developing faults. Various techniques have been reported in literature for induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
12
0
1
Order By: Relevance
“…In the case of regression-based models, these techniques help lower the order of function to be mapped by DL models, which result in computational efficiency and robust real-time deployment. Popular feature selection techniques are principal component analysis (PCA), linear discriminant analysis (LDA), and independent component analysis (ICA) [41,46]. ese techniques are particularly known for their ability to reduce the dimensionality of the dataset.…”
Section: Feature Processing For Dl-based Condition Monitoring Of Motorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of regression-based models, these techniques help lower the order of function to be mapped by DL models, which result in computational efficiency and robust real-time deployment. Popular feature selection techniques are principal component analysis (PCA), linear discriminant analysis (LDA), and independent component analysis (ICA) [41,46]. ese techniques are particularly known for their ability to reduce the dimensionality of the dataset.…”
Section: Feature Processing For Dl-based Condition Monitoring Of Motorsmentioning
confidence: 99%
“…ey found that noninvasive techniques such as thermal imaging are overcoming the conventional condition monitoring methods. On the other hand, in [41] authors have briefly reviewed various condition monitoring techniques particularly based on current, vibration, and acoustic signals. ere is therefore still a need for a comprehensive review on the applications of DL models in condition monitoring of motors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, AI techniques have become increasingly applied in vehicles fault diagnosis due to the significant impact [8]. In this regard, the authors in [9] proposed a self-diagnosis system for autonomous vehicles that aims to improve the self-diagnosis speed and reduce the overhead.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, early fault detection in rotating machines is a goal that ultimately assists in saving system from major damages Generally, a motor requires electric current for rotor to produce torque, which is obtained by electromagnetic induction from magnetic field of stator winding. In various industries 3phase IMs are widely used because these motors are efficient, reliable, compact, less expensive, and easy to operate [6,9]. Three phase motors are also used in electric vehicles and railways owing to its robust structure and high performance [10].…”
Section: Introductionmentioning
confidence: 99%